Abu Bakar As-Siddiq (Islamic Education Management and Its Contribution to Education) (Journal Intellectual Sufism Research (JISR), 2024)
Education is one of the main pillars in Islam, as explained in many verses of the Qur'an and Hadith. Education has an important role in the formation of individuals who have noble character and broad knowledge, so that they are capable carrying out his mandate as caliph on earth. In Islamic education, there are periods educational development which has been going on since the time of the Prophet. After his death Rasulullah, the leadership of the Islamic community is held by the companions of the Prophet, which starts from the companions Abu Bakr Ash-Siddiq. Regarding the figure of Abu Bakar Ash-Siddiq, he is one The most important friend of the Prophet Muhammad SAW and the first caliph of Islam. In terms of This article discusses the biography of Abu Bakar, his contribution to the development of Islam, his work while in leadership, as well as his educational thoughts and practices. apply. Through analysis of various historical sources and Islamic literature, this article aims to provide insight into the dimensions of personality, leadership and thinking Abu Bakar's education is relevant to the current context.Keywords: education, management, Abu Bakar Ash Shiddiq.